2020
DOI: 10.1002/jgm.3242
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA SCARNA2 induces cutaneous squamous cell carcinoma progression via modulating miR‐342‐3p expression

Abstract: Background: Long non-coding RNAs (lncRNAs) play important roles in the progression of tumors. However, the function and expression of SCARNA2 in cutaneous squamous cell carcinoma (cSCC) is still unreported. Methods: A quantitative polymerase chain reaction was applied to study the expression of SCARNA2 and miR-342-3p. Cell counting kit-8, flow cytometry and transwell assays were performed to study cell growth, cycle and cell invasion. Results: We found that SCARNA2 expression is up-regulated in cSCC cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, Zhang et al showed that SCARNA2 mediates colorectal cancer chemoresistance through interaction with mirR-342-3p ( Zhang et al, 2019 ). Ma et al showed that SCARNA2 induces cutaneous squamous cell carcinoma progression by regulating miR-342-3p expression ( Zhang et al, 2020 ). Previous studies have shown that METTL3 methylated SOX2 transcripts, subsequently recognized by the specific m6A “reader” and insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2), to maintain SOX2 stability and promote colorectal carcinoma progression ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhang et al showed that SCARNA2 mediates colorectal cancer chemoresistance through interaction with mirR-342-3p ( Zhang et al, 2019 ). Ma et al showed that SCARNA2 induces cutaneous squamous cell carcinoma progression by regulating miR-342-3p expression ( Zhang et al, 2020 ). Previous studies have shown that METTL3 methylated SOX2 transcripts, subsequently recognized by the specific m6A “reader” and insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2), to maintain SOX2 stability and promote colorectal carcinoma progression ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are defined as non-coding RNAs (ncRNAs) over 200 nucleotides in length and can regulate gene expression at epigenetic, transcriptional, and posttranscriptional levels [ 6 ]. In addition, some lncRNAs have been increasingly recognized to be involved in the progression of cSCC, such as lncRNA TINCR [30993776] and lncRNA SCARNA 2 [ 7 ]. The important role of lncRNA PICSAR in cSCC has been reported by previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The findings reveal that the overexpression of scaRNA2 competes with miR-342-3p by ending up with the high expression of epidermal growth factor receptor, leading to colorectal cancer chemo-resistance (68). Increased expression of scaRNA2 also promotes cell proliferation, migration, and invasion in cutaneous squamous cell carcinoma (69).…”
Section: Role Of Pseudogenes In Llpsmentioning
confidence: 94%